2018
DOI: 10.3389/fpsyg.2018.02500
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Depression and Early Child Development: A Mixed-Methods Study From Rural China

Abstract: Half of rural toddlers aged 0–3 years in China's Qinling Mountainous region are cognitively delayed. While recent studies have linked poor child development measures to the absence of positive parenting behaviors, much less is known about the role that caregiver depression might play in shaping child development. In this paper, a mixed methods analysis is used to explore the prevalence of depression; measure the association between caregiver depression and children's developmental delays, correlates of depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
61
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 76 publications
8
61
3
1
Order By: Relevance
“…Depressed caregivers were more likely to show negative parenting interactions (eg, limited facial and behavioural affect) with their children, and these interactions were directly relevant for children’s development 29 30. A strong negative correlation has been reported between the levels of depression of grandmothers and the levels of developmental outcomes of the grandchildren in their care, including cognitive, language, social-emotional and motor functions 31 32. Taken together, changes in social policies and intervention programmes should be developed to address timely diagnosis and treatment of depression for these people, which will help improve young children’s developmental outcomes in rural China.…”
Section: Discussionmentioning
confidence: 99%
“…Depressed caregivers were more likely to show negative parenting interactions (eg, limited facial and behavioural affect) with their children, and these interactions were directly relevant for children’s development 29 30. A strong negative correlation has been reported between the levels of depression of grandmothers and the levels of developmental outcomes of the grandchildren in their care, including cognitive, language, social-emotional and motor functions 31 32. Taken together, changes in social policies and intervention programmes should be developed to address timely diagnosis and treatment of depression for these people, which will help improve young children’s developmental outcomes in rural China.…”
Section: Discussionmentioning
confidence: 99%
“…These rates are comparable to, and in some cases even higher than, other developing countries, where rates of illness in any given two-week period tend to be around 40-50% for diarrhea [20,21], 10-50% for fever, and 10-20% for coughing spells [22,23]. Research on maternal mental health in China has also discovered rates of depression to be around 20-25% [24][25][26], which is higher than both the 13% global rate of maternal mental disorders and similar to the rate of mental disorders among women in other LMICs (20%) [27].…”
Section: Introductionmentioning
confidence: 63%
“…According to recent studies, the prevalence of mental health issues among caregivers is higher in rural areas of China compared to many other developing countries [ 27 , 28 ]. Previous studies demonstrated that mental health problems affect between 23% and 40% of caregivers of young children in rural China [ 29 , 30 , 31 , 32 ]. This is higher than rates of caregiver mental health issues in other LMICs such as India (23%) [ 33 ] or Vietnam (21%) [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The existing literature has identified, as well, several risk factors for mental health issues among mothers and caregivers in rural China. Qualitative evidence points to poverty-related factors as potential risk factors for depression among rural caregivers [ 30 , 35 ]. In addition, factors such as poor physical health [ 36 ], raising multiple children [ 37 ], and a husband’s not living at home [ 38 ] have been found to be potential risk factors for mental health issues among rural mothers in China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation